Effects of Time-of-Day on Repeated Sprint Performance of Aromatherapy Massage Applied Young Futsal Players - Bayer, Ramazan; Eken, Özgür (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Different protocols are applied in order to increase the performance of athletes in sports that include high-intensity activities such as futsal. Massage protocols applied before or after exercise are frequently used for performance improvement. The differences in oils used in the massage and the time of day may vary performance levels of the futsal players. Aim: This study was planned to determine the effects of time-of-day on repeated sprint performance of aromatherapy massage applied young futsal players. Methods: Twelve male athletes between the age of 18-25, who exercised regularly for five days a week and played futsal for at least 4 years, participated in the study (age, 20.50± 1.78 years; height, 171.92± 2.23 cm; 67.92 ± 2.42 kg; BMI 23.06±.77). The research protocols consisted of three different protocols as single group, non-massage protocol (NM), Swedish massage applied protocol (SM), and aromatherapy massage applied protocol (ATM). In addition, three measurements were taken for each protocol and measurements were made at different times of the day (09.00 in the morning; 13.00 in the afternoon; 17.00 in the evening). After each measurement, the Repetitive Sprint Test (RST) (6x20m) measurements of the athletes were taken. While evaluating RST results, the fastest sprint time (FS), total sprint time and percent change (PC) from the first sprint to the last sprint were calculated. Results: It was determined that there was a statistical difference between RST values observed at different times of the day after NM, SM and ATM protocols. In addition, among all protocols, ATM protocol was found to be more effective. Conclusion: It was determined that ATM had a positive effect on RST performance compared to NM and SM protocols and the ATM protocol applied in the evening was more effective than the ATM protocol applied in the morning and afternoon.